AB1095 Long-term impact of juvenile idiopathic arthritis on quality of life of adult patients in greece. (12th June 2018) - Paskalis, G.C.; Dimopoulou, D.; Trachana, M.; Theocharidou, C.C.; Pratsidou-Gertsi, P.; Oikonomou, T.; Dimitroulas, T.; Garyfallos, A.
Abstract : Background: Juvenile Idiopathic Arthritis (JIA) is the most common rheumatic disease in childhood and affects negatively both physical and psychosocial functioning. Objectives: To explore the long-term impact of JIA on quality of life of adult patients in Northern Greece. Methods: Adult patients with a definite diagnosis of JIA were assessed by the SF-12v2 questionnaire in the outpatient transition (from Paediatric to adult Rheumatology) clinic of Hippokratio Hospital of Thessaloniki. SF-12 questionnaire is a quality of life assessment tool and consists of a Physical Component Summary (PCS) and a Mental Component Summary (MCS). PCS and MCS of the patient group were compared to an age-matched control group, using t-test or Mann-Whitney U test, as appropriate. Moreover, percentages of patients and controls who were severely affected (<45 points in PCS or MCS) were compared, using Chi-squared test . Finally, correlation between the two summary components of SF-12 of patients was measured, using Spearman's rho . Statistical analysis was done using SPSS software. Level of statistical significance is p<0.05. Results: A total of 50 patients and 135 controls were enrolled in the study. The median (IQR) patient age was 32 10 years and disease duration was 24 9, 5 years. PCS scores of patients group were statistically significantly lower compared to control group (p=0.021) and more patients than controls scored low values (<45) in PCS (22% versus 6.7%, odds ratio, 4.0 [95% CI, 1.5, 10.2]; p=0.007). MCS scores of patients were slightly better than scores of controls (mean difference, 3.67 [95% CI, 0.44, 6.90]; p=0.026), but the severely affected were similar in both groups (odds ratio, 0.6 [95% CI, 0.3, 1.2]; p=0.174). No correlation between PCS and MCS was found (p=0.48). Conclusions: There is an apparent impact of JIA on many patients' quality of life, specifically in terms of their physical health, that persists for many years after disease onset, which is in line with studies from other countries. This could be related to disease severity, disease subtype and duration, socioeconomic status and availability of treatment options. Interestingly, JIA wasn't found to affect the patients' mental health. A more specific psychometric test would be appropriate for in-depth analysis and confirmation of this result. Study design did not allow subgroup analysis according to JIA subtype, disease severity or duration, highlighting the need for long-term outcome studies focusing on the risk factors which may be involved. References: [1] Foster H, et al. Outcome in adults with juvenile idiopathic arthritis: A quality of life study. Arthritis & Rheumatism. 2003;48(3):767–775 [2] Kontodimopoulos N, et al. Validity of SF-12 summary scores in a Greek general population. Health Qual Life Outcomes. 2007Sep 28;5:55 [3] Minden K, et al. Long-term outcome in patients with juvenile idiopathic arthritis. Arthritis & Rheumatism. 2002;46(9):2392–2401 [4] Anink J, et al. Long-term quality of life and functional outcome of patients with juvenile idiopathic arthritis in the biologic era: a longitudinal follow-up study in the Dutch Arthritis and Biologicals in Children Register. Rheumatology. 2015;54(11):1964–1969 Disclosure of Interest: None declared